2016
DOI: 10.1164/rccm.201510-1942oc
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Continuous Positive Airway Pressure on Glycemic Control in Patients with Obstructive Sleep Apnea and Type 2 Diabetes. A Randomized Clinical Trial

Abstract: Among patients with suboptimally controlled type 2 diabetes and OSA, CPAP treatment for 6 months resulted in improved glycemic control and insulin resistance compared with results for a control group. Clinical trial registered with www.clinicaltrials.gov (NCT01801150).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
122
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(142 citation statements)
references
References 49 publications
6
122
3
Order By: Relevance
“…OSA and dysglycemia limited impact on improvement of glycemic control in patients with T2DM [12][13][14][15], although the effect of CPAP therapy on glycemic control depends on adherence to therapy. Thus, although we confirmed that the severity of OSA is associated with HbA1c level in Japanese nondiabetic individuals, the impact of OSA on glycemic control in Japanese patients with T2DM needs further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…OSA and dysglycemia limited impact on improvement of glycemic control in patients with T2DM [12][13][14][15], although the effect of CPAP therapy on glycemic control depends on adherence to therapy. Thus, although we confirmed that the severity of OSA is associated with HbA1c level in Japanese nondiabetic individuals, the impact of OSA on glycemic control in Japanese patients with T2DM needs further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…One large randomized clinical trial of PAP therapy in adults with T2DM and SDB showed no effect on HbA1c, but was limited by PAP adherence in only 61.3% of subjects, and an elevated mean residual AHI of 6.2 [5]. In contrast to this, another recent randomized trial of PAP therapy in adults with T2DM and SDB did show a significant reduction in HbA1c [6]. PAP adherence in this study was markedly higher (77%) compared to the prior study.…”
Section: Discussionmentioning
confidence: 91%
“…MARTINEZ-CERON et al [14] have shown that 6 months, but not 3 months of CPAP treatment significantly reduced HbA1c levels in 50 patients with OSA, type 2 diabetes mellitus and baseline HbA1c ⩾6.5% compared with conservative therapy. PAMIDI et al [28] randomised 39 participants with OSA and pre-diabetes to receive either 8 h nightly CPAP or oral placebo for 2 weeks, and found that CPAP treatment improved glucose metabolism compared with placebo.…”
Section: Discussionmentioning
confidence: 97%
“…One very recent meta-analysis of seven studies with a total of 794 patients reported that all the trials predominantly recruited male patients, with a mean percentage of 74% male [12]. Similarly, the effect of CPAP on glucose and lipid metabolism has also been assessed in cohorts in which women usually accounted for <30-40% of the whole sample [14,[27][28][29][30]. Given that OSA differs between women and men, it cannot be taken for granted that the findings obtained in males can be translated to women.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation